Analysing frugal innovation incubation programmes: a case study from the water sector. (1st June 2020) - Mvulirwenande, Silas; Wehn, Uta
Abstract : Perceived positive impacts of frugal innovation for sustainable global development have triggered a variety of programmes to foster such innovation. To increase the impact of these programmes, it is important to understand how they function. In this paper, we develop a conceptual framework for the analysis of interventions that foster frugal innovations through incubation. Drawing on relevant theories and concepts in the field of innovation and related literature, the framework is based on two major categories of factors influencing the nature and outcome of frugal innovation incubation. The first category relates to the incubation process, the second to the innovation environment. The proposed framework is applied to the case study of VIA Water, a Dutch programme to foster water innovation in African cities. The framework and the case study presented in this paper demonstrate the complexity of a frugal innovation incubation process and thus the need to take a holistic approach when designing and/or analysing related interventions. We conclude that frugal innovation incubation programmes should consider that the innovation capabilities of potential frugal innovators tend to be weaker in developing than in developed countries. Therefore, incubation programmes should devise strategies that present frugal innovators possessing local knowledge and creative ideas with a realistic chance of competing.